The Role of Profitability in Mediating the Relationship Between Liquidity on Stock Prices for the Period 2013-2022 - Rizal Pradana Putra; Bambang Mahmudi; Emma Suryani (Institute of Advanced Knowledge and Science, 2024)
This study explores how the Net Profit Margin (NPM) acts as an intermediary in the connection between the Current Ratio (CR) and stock returns for companies included in the LQ45 Index over the period from 2013 to 2022. The study population includes all companies within the LQ45 Index, which totals 45 firms. The LQ45 Index features a group of companies with the highest liquidity in their stock performance on the Indonesia Stock Exchange (IDX). To be included, companies must have significant market capitalization, impressive stock performance over time, and strong financial health. Consequently, the LQ45 Index is highly favored by investors. Using Purposive Sampling, the sample is limited to companies that have been continuously listed on the LQ45 Index throughout the 10-year span and have the requisite data, leading to a selection of 19 companies. Analytical methods employed include Descriptive Statistical Analysis, Multiple Linear Regression, Path Analysis, and the Sobel Test, with IBM SPSS25 used for data analysis. In this research, the Current Ratio (CR) serves as the independent variable, Stock Return is the dependent variable, and the Net Profit Margin (NPM) acts as the mediating variable. Findings reveal that the Current Ratio does not significantly impact Stock Return, the Net Profit Margin has a positive and significant effect on Stock Return, the Current Ratio negatively and significantly affects the Net Profit Margin, and the Net Profit Margin fully and significantly mediates the impact of the Current Ratio on Stock Return.